176k views
3 votes
Help please I don’t get this

Help please I don’t get this-example-1
User Aniyah
by
6.0k points

2 Answers

2 votes

Answer:

C. This can be found by looking at when x=0. If y=-1, then that means that the y intercept is -1, so plug in 1 to either one of the middle two equations and see if it works.

Explanation:

User Ermat Alymbaev
by
6.0k points
6 votes

Answer:

y = -2x - 1

Explanation:

Formula is y = mx + b

m = slope

slope = change in y/change in x = (-1 - 3) / (0 - -2) = -4/2 = -2

So equation is now y = -2x + b

To find b, substitute any value from the table into the equation. Let's use (-2,3)

y = -2x + b

3 = -2(-2) + b

3 = 4 + b

-1 = b

So equation is y = -2x - 1

User Chetter Hummin
by
5.3k points